1997
DOI: 10.1243/0957650971537312
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation of a centrifugal compressor with hub vane diffusers

Abstract: The present investigation reports results of experimental studies on a centrifugal compressor equipped with hub vane diffusers. The diffuser vane height ( h/b) is varied as follows: 0 (vaneless), 0.2, 0.3, 0.4 and 1 (vane). The experiments were carried out on a low specific speed centrifugal compressor with a radial tipped impeller with an inducer at the inlet. The measurements consist of determining performance characteristics, measuring static pressures on the hub and shroud and flow traverses with a precali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The speed of the compressor can be maintained constant at §1 r/min. The compressor was earlier used for investigations on partial vane diffusers [2].…”
Section: Experimental Facilitymentioning
confidence: 99%
“…The speed of the compressor can be maintained constant at §1 r/min. The compressor was earlier used for investigations on partial vane diffusers [2].…”
Section: Experimental Facilitymentioning
confidence: 99%
“…During the past years, some investigations have been carried out to study the half vane diffuser in centrifugal compressors. The results showed that this diffuser could improve the stage performance 8–10 . Yoshinaga et al 8 proposed a diffuser with half vanes in a centrifugal compressor and the test result showed that the pressure recovery of this diffuser at distorted inlet flow is considerably improved.…”
Section: Introductionmentioning
confidence: 95%
“…In contrast, Liu et al [7] found that a hub-side vaned diffuser has higher pressure recovery and efficiency than a vaneless diffuser and has a wider operating range compared with a traditional vaned diffuser. Sitaram et al [8] showed that a hub-side vaned diffuser has a higher energy coefficient and a wider operating range under a certain vane height. The experimental and simulation investigations by Ohta et al [9] indicated that the tapered vaned diffuser could reduce noise and enlarge the stable operating ranges by vortex control.…”
Section: Introductionmentioning
confidence: 99%